(-)-7-O-acetylgoniodiol as cancer chemopreventive agent from Goniothalamus Griffithii - Kampong R. (2014)
(-)-7-O-Acetylgoniodiol (1B) together with goniothalamin (2) and pinocembrin (3), have been isolated from leaves and twigs of Goniothalamus griffithii. All compounds were identified by spectroscopic analyses and comparison with published data. 1B can be formed by recrystallization from EtOH/acetone and its stereochemistry was further confirmed by X-ray crystallographic analysis. Goniothalamin exhibited most potent cytotoxicity against P-388, KB, Col-2, MCF-7, Lu-1, A549, T24, ASK, HEK-293 and cells with ED50 values of 0.19, 0.56, 0.36, 0.56, 0.54, 0.67, 0.39, 0.67 and 0.50 μg/mL, respectively. In addition, 1B was also showed high selective inhibitory effect on the P-388, KB and HEK-293 with ED50 values of 3.31, 3.26 and 1.89 μg/mL.